(untitled) (Al-Mansour Journal, 2023)
The Advanced Encryption Standard (AES) are one of the most algorithms used in symmetric key cryptography. Finalist candidate algorithms are five AES algorithms they are :MARS, RC6, Rijndael , Serpent, and Twofish. The paper evaluate three algorithms which are Rijndael, Serpent, and Twofish. The reason of chosen these three algorithms are :they have fixed block size of 128 bits and a key size of 128, 192, or 256 bits. We implement these algorithms in two kinds of computers: desktop pc. (Samsung 3GB) and laptop pc. (Intel core2 2GB).The time required for decryption and encryption Are Measured and the results are compared for the three algorithms we find that Rijndael is the best.